Distribution and relative abundance of striped dolphins, and distribution of sperm whales in the Ligurian Sea cetacean sanctuary: results from a collaboration using acoustic monitoring techniques - Gordon, J.C.D.; Matthews, J.N.; Panigada, S.; Gannier, A.; Borsani, J.F.; Notarbartolo di Sciara, G. (J. Cetacean Res. Manage., 2000)
The distribution and relative abundance of groups of striped dolphins (Stenella coeruleoalba) in the Ligurian Sea cetacean sanctuary, based on acoustic surveys carried out in the summers of 1994-1996, is presented. Abundance indices based on acoustic detections were adjusted for covariates likely to influence the detectability of dolphin vocalisations, such as wind speed, background noise and sea state. Dolphin vocalisation rates were shown to vary diurnally, being higher at night, and this effect was also modelled and removed. Results showed that dolphin groups were fairly evenly distributed throughout the sanctuary, but they were more abundant in offshore waters, peaking at water depths between 2,000-2,500m. Preliminary sightings results also indicated larger-sized groups in offshore regions. Relative abundance does not appear to vary significantly over the summer months. Sperm whales (Physeter macrocephalus) were detected at 4% of monitoring stations, representing at least 61 different group encounters. Although not common, they appeared to be widely distributed in deep water throughout the study area.